2016
DOI: 10.1016/j.nlm.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D1 receptor knockout on fear and reward learning

Abstract: Dopamine signaling is involved in a variety of neurobiological processes that contribute to learning and memory. D1-like dopamine receptors (including D1 and D5 receptors) are thought to be involved in memory and reward processes, but pharmacological approaches have been limited in their ability to distinguish between D1 and D5 receptors. Here, we examine the effects of a specific knockout of D1 receptors in associative learning tasks involving aversive (shock) or appetitive (cocaine) unconditioned stimuli. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For example, mice lacking the dopamine D1 receptor (D1R) in granule cells of the dentate gyrus and the striatum exhibit poor retention of contextual fear (Ikegami et al, 2014; Sarinana et al, 2014). However, studies examining the impact of global D1R deletion on contextual fear memory have yielded mixed results (Ortiz et al, 2010; Abraham et al, 2016), which may be explained by methodological differences as well as the possibility of recruitment of compensatory pathways. Importantly, with respect to generalization, mice lacking D1R in the dentate gyrus are unable to discriminate between the training context and a novel context after exposure to contextual fear conditioning (Sarinana et al, 2014), while a modest increase in contextual fear generalization is observed when D1R is globally deleted (Abraham et al, 2016).…”
Section: Molecular and Cellular Mechanisms Of Fear Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mice lacking the dopamine D1 receptor (D1R) in granule cells of the dentate gyrus and the striatum exhibit poor retention of contextual fear (Ikegami et al, 2014; Sarinana et al, 2014). However, studies examining the impact of global D1R deletion on contextual fear memory have yielded mixed results (Ortiz et al, 2010; Abraham et al, 2016), which may be explained by methodological differences as well as the possibility of recruitment of compensatory pathways. Importantly, with respect to generalization, mice lacking D1R in the dentate gyrus are unable to discriminate between the training context and a novel context after exposure to contextual fear conditioning (Sarinana et al, 2014), while a modest increase in contextual fear generalization is observed when D1R is globally deleted (Abraham et al, 2016).…”
Section: Molecular and Cellular Mechanisms Of Fear Generalizationmentioning
confidence: 99%
“…However, studies examining the impact of global D1R deletion on contextual fear memory have yielded mixed results (Ortiz et al, 2010; Abraham et al, 2016), which may be explained by methodological differences as well as the possibility of recruitment of compensatory pathways. Importantly, with respect to generalization, mice lacking D1R in the dentate gyrus are unable to discriminate between the training context and a novel context after exposure to contextual fear conditioning (Sarinana et al, 2014), while a modest increase in contextual fear generalization is observed when D1R is globally deleted (Abraham et al, 2016). Finally, cued fear memory may or may not be affected by D1R deletion (Ortiz et al, 2010; Sarinana et al, 2014; Abraham et al, 2016), which may be attributed to methodological differences in the studies.…”
Section: Molecular and Cellular Mechanisms Of Fear Generalizationmentioning
confidence: 99%
“…Several lines of evidence show that dopamine D1 receptors expressed in the NAc, the PFC, hippocampus and the amygdala play a critical role in fear learning and fear extinction (Abraham et al, 2016a;2016b;Borowski and Kokkinidis, 1998;Fadok et al, 2009;Hikind and Maroun, 2008;J. J. Li et al, 2018;Ng et al, 2018).…”
Section: Obesogenic Diet Leads To Abnormal Maturation Of the Neural Amentioning
confidence: 99%
“…However, CPP is also decreased in animals lacking D1R (Abraham et al . ). Results obtained with constitutive Go1+2α‐/‐ mice suggest that CPP requires Go1α to develop, probably using either D1R or D2R.…”
Section: Discussionmentioning
confidence: 97%
“…In this line, CPP is nearly abolished in D2R knock out animals (Welter et al 2007). However, CPP is also decreased in animals lacking D1R (Abraham et al 2016). Results obtained with constitutive Go1+2a-/-mice suggest that CPP requires Go1a to develop, probably using either D1R or D2R.…”
Section: Differing Effects Of Go1a and Go2a On Psychostimulantinducedmentioning
confidence: 90%